Improved Photoactivities of Large‐surface‐area g‐C3N4 for CO2 Conversion by Controllably Introducing Co‐ and Ni‐Species to Effectively Modulate Photogenerated Charges. Issue 24 (5th November 2019) - Zhang, Xuliang; Zhang, Xinxin; Ali, Wajid; Chen, Xiaowei; Hu, Kang; Li, Zhijun; Qu, Yang; Bai, Linlu; Gao, Yiwen; Jing, Liqiang
Abstract: Simultaneously modulating photogenerated electrons and holes by introducing transitional metals species on carbon nitride (g‐C3 N4 ) are highly desired for effectively photocatalytic converting CO2 . Herein, a cyanuric acid‐melamine preassembled approach is developed to obtain large‐surface‐area g‐C3 N4 with high photoactivity for CO2 conversion, and its photoactivity is improved by controllably modifying Co‐species during the synthetic process of g‐C3 N4, attributed to its hole capture capability and catalytic capability for water oxidation. Moreover, the photoactivity is further improved by decorating Ni‐species on g‐C3 N4, attributed to its electron capture capability and catalytic capability for CO2 reduction. Noticeably, simultaneously modulating holes and electrons displays a noticeable synergy on improving photocatalytic activities. Interestingly, the photoactivity of amount‐optimized Co and Ni co‐modified g‐C3 N4 is 3.1‐time higher than that of pristine g‐C3 N4, with the quantum efficiency improvement of 4.5 time at 405 nm. This work will provide a feasible way of simultaneously modulating electrons and holes to fabricate high‐performance g‐C3 N4 ‐based nano‐sized photocatalysts for CO2 conversion. Abstract : Photocatalysis : Co‐ and Ni‐species modified on the surface of CN can respectively modulate the photogenerated holes and electrons, leading to promoted charge separation along with improved photocatalytic activities.